Studies on Surface Tension of Titanium(III) Soaps in Mixed Organic Solvents - VERMA, H.S.; KUMAR, VINOD (Asian Journal of Chemistry, 2010)
Surface tension of titanium soaps solutions in mixed organic solvents has been measured at 313 K and the data have been discussed on the basis of Langmuir’s approximate equation γ = γ0 (1 + x ln·γ) – γo x ln c The critical micelle concentration (CMC) values obtained from γ -log C plots, decrease with increasing chain length of soap. Constant χ depends on chain length of soap. Constant γ above CMC increase with increasing chain length, but do not show any definite trend above this concentration. Surface alloys covered by the soap micelles formed by male of soap have also been evaluated.